The persistence of weapons: Global evidence - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
This study investigates persistence (or hysteresis) in weapons using a panel of 163 countries for the period 2010 to 2015. The following are some main findings. (i) Compared to countries that are landlocked, persistence in heavy weapons is more apparent in nations that are open to the sea. (ii) Relative to the Middle East & North Africa (MENA), heavy weapons is more persistent in the East Asia and the Pacific countries. This tendency is consistent with "weapons imports". (vi) Evidence of persistence is not very apparent in "weapons imports" with the exception of the fact that it is higher in low income countries, compared to their high income counterparts. Hence, there is less hysteresis in weapons exports when compared with heavy weapons when weapons exports. (v) The determinants of persistence employed in the conditioning information set are contingent on fundamental characteristics and panels. Policy implications are discussed.
Keywords: H56; L64; K42; P50; 330; War; Armaments; Global evidence; Persistence